Infant feeding practice and childhood cognitive performance in South India. Issue 5 (27th November 2009) - Veena, Sargoor R; Krishnaveni, Ghattu V; Srinivasan, Krishnamachari; Wills, Andrew K; Hill, Jacqueline C; Kurpad, Anura V; Muthayya, Sumithra; Karat, Samuel C; Nalinakshi, Mahadevu; Fall, Caroline H D
Abstract : Aim: Several studies have suggested a beneficial effect of infant breastfeeding on childhood cognitive function. The main objective was to examine whether duration of breastfeeding and age at introduction of complementary foods are related to cognitive performance in 9- to 10-year-old school-aged children in South India. Methods: The authors examined 514 children from the Mysore Parthenon birth cohort for whom breastfeeding duration (six categories from <3 to ≥18 months) and age at introduction of complementary foods (four categories from <4 to ≥6 months) were collected at the first-, second- and third-year annual follow-up visits. Their cognitive function was assessed at a mean age of 9.7 years using three core tests from the Kaufman Assessment Battery for children and additional tests measuring long-term retrieval/storage, attention and concentration, visuo-spatial and verbal abilities. Results: All the children were initially breastfed. The mode for duration of breastfeeding was 12–17 months (45.7%) and for age at introduction of complementary foods 4 months (37.1%). There were no associations between longer duration of breastfeeding, or age of introduction of complementary foods, and cognitive function at 9–10 years, either unadjusted or after adjustment for age, sex, gestation, birth size, maternal age, parity, socio-economic status, parents' attained schooling and rural/urban residence. Conclusions: Within this cohort, in which prolonged breastfeeding was the norm (90% breastfed ≥6 months and 65% breastfed for ≥12 months), there was no evidence suggesting a beneficial effect of longer duration of breastfeeding on later cognitive ability.